World Bank Crisis Simulation Exercises : What Is at Stake in Coordinating and Making Decisions in a Crisis - Almansi, Aquiles; Lee, Yejin Carol; Todoroki, Emiko (World Bank, Washington, DC, 2016)
The FIRST Lessons Learned Series is a collection of FIRST’s technical and functional insights gained from FIRST funded engagements. This Knowledge Note, shares insights on Crisis Simulation Exercise, drawn from the experience of delivering these exercises and addresses the key factors that financial sector authorities might find useful in their efforts to prepare for and manage a potential crisis.